2022
DOI: 10.1371/journal.pone.0266663
|View full text |Cite|
|
Sign up to set email alerts
|

Infectious diseases, comorbidities and outcomes in hospitalized people who inject drugs (PWID)

Abstract: Injection drug use poses a public health challenge. Clinical experience indicates that people who inject drugs (PWID) are hospitalized frequently for infectious diseases, but little is known about outcomes when admitted. Charts were identified from local hospitals between 2013–2018 using consultation lists and hospital record searches. Included individuals injected drugs in the past six months and presented with infection. Charts were accessed using the hospital information system, undergoing primary and secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…This finding is in line with the current literature, reporting that PWUDs, especially those with HCV diagnosis, are frequently hospitalized. 28,29 These results should be interpreted taking some limitations into account, above all lying in its observational design and the unavoidable flaws of the use of data retrieved from administrative databases. In fact, this approach might lead to a potential underestimation of clinical information on comorbidities and/or concomitant treatments that cannot be extrapolated from the database (also because underreported by patients) together with other potential confounding factors that might have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with the current literature, reporting that PWUDs, especially those with HCV diagnosis, are frequently hospitalized. 28,29 These results should be interpreted taking some limitations into account, above all lying in its observational design and the unavoidable flaws of the use of data retrieved from administrative databases. In fact, this approach might lead to a potential underestimation of clinical information on comorbidities and/or concomitant treatments that cannot be extrapolated from the database (also because underreported by patients) together with other potential confounding factors that might have affected the results.…”
Section: Discussionmentioning
confidence: 99%
“…The comorbid cardiac conditions associated with severe bacterial infection among IVDUs are hypertension, thrombosis (deep vein thrombosis, pulmonary embolism), congestive heart failure, and valvular conditions [ 9 ]. S. aureus is the most common bacterial infection leading to infective endocarditis [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…Prolonged immobilization among IVDUs due to impairment in consciousness increases the risk of DVT and pressure ulcers, leading to infections [ 27 ]. Underlying local and distant site tissue damage helps create a favorable environment for the adherence and proliferation of bacteria [ 9 ]. The valvular conditions with damaged valves or prosthetic valves are prone to infections with Staphylococcus epidermidis , viridans streptococci, and Streptococcus bovis due to turbulence-mediated endothelial damage [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…A national U.S. study identified nearly nine times the risk of COVID-19 diagnosis among patients with substance use disorders (SUD) compared to those without SUD [ 2 ]. Among people who inject drugs (PWID), multilevel factors elevate the risk of SARS-CoV-2 infection, hospitalization, and death, including chronic and infectious disease comorbidities [ 2 , 3 ], stigma, and other structural factors (e.g., homelessness, poverty, limited transportation, and health insurance) that reduce utilization of preventive screening and healthcare services [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%